2022
DOI: 10.1186/s13643-022-02085-1
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the unassisted physical exam conducted over synchronous audio-video telemedicine

Abstract: Background This scoping review aims to provide a broad overview of the research on the unassisted virtual physical exam performed over synchronous audio-video telemedicine to identify gaps in knowledge and guide future research. Methods Searches for studies on the unassisted virtual physical exam were conducted in 3 databases. We included primary research studies in English on the virtual physical exam conducted via patient-to-provider synchronous,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Further contributing to the mounting evidence to support incorporation of virtual physical examination maneuvers, two recently published scoping reviews of the literature have both concluded that the virtual physical examination has similar diagnostic accuracy and is largely equivalent to the in-person examination. 13 , 15 However, when considering the available data regarding the quality and value of the in-person physical examination, it raises the question of whether this should really be the gold standard in the first place. This is a topic garnering increasing attention, as leading authors in the field of digital health have begun to call for the development of a new “21st century” physical examination.…”
Section: Patient–provider Interactionmentioning
confidence: 99%
“…Further contributing to the mounting evidence to support incorporation of virtual physical examination maneuvers, two recently published scoping reviews of the literature have both concluded that the virtual physical examination has similar diagnostic accuracy and is largely equivalent to the in-person examination. 13 , 15 However, when considering the available data regarding the quality and value of the in-person physical examination, it raises the question of whether this should really be the gold standard in the first place. This is a topic garnering increasing attention, as leading authors in the field of digital health have begun to call for the development of a new “21st century” physical examination.…”
Section: Patient–provider Interactionmentioning
confidence: 99%
“…Furthermore, while previous studies comparing virtual and in-person physical exams have concluded that they may be equivalent, an in-person physical examination is sometimes necessary to evaluate the patient properly [ 48 ]. For example, new onset back pain would require an examination to evaluate for epidural disease and spinal cord compromise.…”
Section: Barriers To Telemedicinementioning
confidence: 99%
“…Although telemedicine has existed for decades, its use remained limited across physicians until the COVID-19 pandemic, during which changes in reimbursement and regulatory frameworks expedited the adoption of real-time audio-video platforms to provide medical services [4][5][6]. As the impact of telemedicine has reached a variety of specialties [7,8] and public awareness of its convenience has increased, many speculate that providers will continue to offer telemedicine options for some services in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine has been explored in a variety of uses, including but not limited to patient examination [7], teleconsultation [8], telesurgery [9] and medical education [10]. However, many users still do not view telemedicine as a substitute for in-person care; physicians cited limitations in diagnostic ability [11] and training [12][13][14], whereas patients cited limited interactivity and difficulty of access [15].…”
Section: Introductionmentioning
confidence: 99%